From Biological Control to Invasion: The Ladybird Harmonia Axyridis as a Model Species
DOI: 10.1007/978-1-4020-6939-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mortality by entomophages on exotic Harmonia axyridis versus native Adalia bipunctata in semi-field conditions in northern Italy

Abstract: A semi-field experiment was carried out in two peach orchards in northern Italy to assess mortality due to predators and parasitoids on the exotic coccinellid Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) in comparison with the native coccinellid Adalia bipunctata L. (Coleoptera: Coccinellidae). The experiments were conducted in cages to avoid the possible escape of the exotic ladybird (not yet established in Italy). Two kinds of cage experiments were included: 'exclusion cages' (access by walking pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Most frequently only qualitative assessment of the diet of predators has been determined, either through direct observation of predation events or identification of prey remnants in predator's alimentary tract or faeces (Harwood and Obrycki 2005;Michalski et al 2011). An attempt to quantify the effect of invertebrate predators on H. axyridis and the two-spot ladybird, Adalia bipunctata (L.), was made in northern Italy by Burgio et al (2008). Using outdoor cage experiments, they found that the rate of predation on H. axyridis eggs did not exceed 2%, while up to 40% of the eggs of A. bipunctata were consumed or destroyed.…”
Section: Predators Of Harmonia Axyridismentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently only qualitative assessment of the diet of predators has been determined, either through direct observation of predation events or identification of prey remnants in predator's alimentary tract or faeces (Harwood and Obrycki 2005;Michalski et al 2011). An attempt to quantify the effect of invertebrate predators on H. axyridis and the two-spot ladybird, Adalia bipunctata (L.), was made in northern Italy by Burgio et al (2008). Using outdoor cage experiments, they found that the rate of predation on H. axyridis eggs did not exceed 2%, while up to 40% of the eggs of A. bipunctata were consumed or destroyed.…”
Section: Predators Of Harmonia Axyridismentioning
confidence: 99%
“…Individual larval instars, however, were preyed on at similar rates in both species. The cage method (sensu Burgio et al 2008) can provide some estimation of the overall predation but it cannot indicate with certainty which predators are involved. The effectiveness and prey preference of individual predators are often assessed in laboratory experiments, and this also applies to predation on ladybirds, including H. axyridis (HoughGoldstein et al 1996;Yasuda and Kimura 2001;De Clercq et al 2003;Santi and Maini 2006;Sloggett 2010a;Průchová et al 2014;Veselý et al 2016).…”
Section: Predators Of Harmonia Axyridismentioning
confidence: 99%
“…Many studies have documented invaders that show a superior ability to exploit local resources as compared with native residents (Bazzocchi et al, 2004;Burgio et al, 2008;Holway, 1998) or as compared with non-invading introduced species. The Argentine ant (Linepithema humile) is not only an agricultural and house pest but is also competitively superior to the native ant species in both interference and exploitative competition in the riparian woodlands of northern California and in the alteration of plant community structure (Holway, 1998;Suarez et al, 2008).…”
Section: Autochthonous Species Competitivenessmentioning
confidence: 99%
“…The exotic coccinellid Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) was intentionally introduced into Northern Italy in the 1990s for the biological control of aphids and psyllids (Bazzocchi et al, 2004;Burgio et al, 2008). At present this species is established in several areas of Northern and Central Italy and is spreading (Burgio et al, 2008;Croci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At present this species is established in several areas of Northern and Central Italy and is spreading (Burgio et al, 2008;Croci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%